Pembentukan Peraturan Negeri Tentang Pengelolaan Sumber Daya Pesisir di Negeri Mamala Kecamatan Leihitu Kabupaten Maluku - La Ode Angga; Muchtar Anshary Hamid Labetubun; Sabri Fataruba (Faculty of Law, Universitas Pattimura, 2023)
Introduction: People on small islands generally depend on natural products such as fishing, gardens, or hamlets.Purposes of Devotion: Carrying out the preparation/making of State Regulations in the management of coastal natural resources in Mamala, Leihitu District, Central Maluku Regency, participants/indigenous communities have more knowledge and understanding regarding the formation of State regulations in the field of management of coastal natural resources and small islands.Method of Devotion: The implementation method used in the realization of Counseling Counseling is carried out by the method of lectures and discussions on Mamalah State Regulations related to coastal natural resource management.Results of the Devotion: In implementing the superior product development program, the following steps were carried out: In the first stage, the Team presented the concepts for the formation of State Regulations concerning the Management of Coastal Resources in Mamala State, Leihitu District, Central Maluku Regency. The second step is to assist in the preparation of the Formation of State Regulations Concerning Coastal Resource Management in Leihitu District, Central Maluku Regency.